Land use/land cover change detection and prediction in the north-western coastal desert of Egypt using Markov-CA. (September 2015) - Halmy, Marwa Waseem A.; Gessler, Paul E.; Hicke, Jeffrey A.; Salem, Boshra B.
Abstract: Detecting land-use change has become of concern to environmentalists, conservationists and land use planners due to its impact on natural ecosystems. We studied land use/land cover (LULC) changes in part of the northwestern desert of Egypt and used the Markov-CA integrated approach to predict future changes. We mapped the LULC distribution of the desert landscape for 1988, 1999, and 2011. Landsat Thematic Mapper 5 data and ancillary data were classified using the random forests approach. The technique produced LULC maps with an overall accuracy of more than 90%. Analysis of LULC classes from the three dates revealed that the study area was subjected to three different stages of modification, each dominated by different land uses. The use of a spatially explicit land use change modeling approach, such as Markov-CA approach, provides ways for projecting different future scenarios. Markov-CA was used to predict land use change in 2011 and project changes in 2023 by extrapolating current trends. The technique was successful in predicting LULC distribution in 2011 and the results were comparable to the actual LULC for 2011. The projected LULC for 2023 revealed more urbanization of the landscape with potential expansion in the croplands westward and northward, an increase in quarries, and growth in residential centers. The outcomes can help management activities directed toward protection of wildlife in the area. The study can also be used as a guide to other studies aiming at projecting changes in arid areas experiencing similar land use changes. Highlights: Random forests potential for mapping deserts' LULC using spectral & ancillary data. Stages of change in LULC of Egyptian northwestern desert due development activities. Markov-CA approach merit for projecting future land use changes in arid regions. Understanding changes in LULC can help guide conservation planning in arid regions.